The midnight heist : the seventeenth adventure in the Kingdom of Fantasy - Stilton, Geronimo (Stilton, Geronimo. Kingdom of Fantasy, 2025)
"I, Geronimo Stilton, had been called back to the Kingdom of Fantasy once more. This time, my help was needed in the Kingdom of Art. Someone had been kidnapping the subjects of the world's most famous paintings. It was up to me to track them down and restore them to their proper mousterpieces"--